Incidencia de la Bailoterapia en el autoestimas de las personas - Guaranga Ilbay, Darwin Dario (2022)
The lack of self-esteem is an aggravating factor in the mental health of the world population, knowing the state of mental health, especially in economically active adult populations, is essential to improve the quality of life of this age group, however, there are not studies about this problem in the city of Riobamba. In the present investigation we have tried to determine the incidence of dance therapy on self-esteem. The following study was carried out in the city of Riobamba, in the Bellavista sector with the "Street Dance" dance therapy group, using a quasi-experimental design with a quantitative approach, whose population and sample was 19 people, 18 female and 1 male, the technique that was applied was a questionnaire and the Rosenberg Scale was chosen as the instrument, applied in a pre and post-test, to determine both the basal levels and the post intervention levels of dance therapy. A dance therapy program was developed that lasted 13 weeks, in which interventions were performed on Thursdays and Saturdays from 7am to 8am, using different dance rhythms: salsa, merengue, cumbia, reggaeton and national rhythms, after the 26 interventions were completed, the Rosenberg questionnaire was applied again to evaluate the effect of the dance therapy program on the intervened population. The data obtained were analyzed using the IBM SPSS software that allowed us to perform the tabulation, when comparing the pre and post test data it was determined that dance therapy did not obtain significant changes in self-esteem, due to different factors such as: acoustic problems at the time of performing dance therapy, inclement weather, stereotypes and stigmas in relation to physical appearance, which determines that dance therapy in our study did not have a positive impact on self-esteem.